Efecto del consumo de polimnia sonchifolia (yacón) sobre los niveles de lípidos en estu- diantes con sobrepeso y obesidad de una universidad privada, Lima, 2012 - Pérez Fernández, Pedro (2019)
The aim of the study was to determine the effects of consumption of Polimnia sonchifolia (Yacon) on lipid levelsin overweight and obese students. Study pre-type experimental design pre test and post test with a single group,slitting. The sample were young people aged between 18-30 years living in private universities. be a total of 41students, of whom 27 were women and 14 men. The sampling was not probabilistic convenience, who for 30 dayswere given 150 g. consumption of yacon for fasting. Then there was the blood lipid profile DEJER laboratories, forlevels of total cholesterol, LDL, HDL, and triglycerides. Likewise Anthropometric assessment: weight and height.The data analysis used was the “t” Student with a significance level of α = 0.05%. The mean plasma total cholesterol in people before consuming the yacon was 199.5122 mg / dl. And at the end of the investigation the averageplasma cholesterol of people was 186.1220 mg / dl. Concluding that the consumption of yacon, reduces cholesterolsignificantly